OPTIMIZING FINANCIAL ADMINISTRATION MANAGEMENT SYSTEM AT TAPALANG SUB-DISTRICT OFFICE - Hasrianti Hasrianti; Nur Fajariani; Jamaludin Kamarudin (Jurnal Ekonomi, 2023)
This research investigates financial management practices at Tapalang Subdistrict Office. Through interviews and documentation analysis, the study examines the source of funds, reception processes, financial management systems, reporting methods, and the use of financial applications. Findings reveal that the organization's funding originates from Mamuju District APBD, with a 10% allocation based on the Budget Implementation Document (DPA). The reception process involves precise calculations, while the financial system relies on the DPA and quarterly cash budgets. Financial reporting employs the General Helper Book (BKU) and integrates data into the regional SIPD application. These insights provide a comprehensive understanding of Tapalang Subdistrict Office's financial operations and contribute to enhancing financial management practices.